A CROSS-SECTIONAL COMPARISON OF MINERALS IN PSYCHIATRIC DISORDER - Ambad, Ranjit S.; Butola, Lata Kanyal; Butola, Lata Kanyal; Singh, Brij Raj; Bankar, Nandkishor; Ghogare, Ajinkya S.; Patil, Ragini (International Journal of Psychosocial Rehabilitation, 2020)
The burden of mental disorders with onset in childhood and adolescence decreased by varying degrees for the individual disorders, and this decrease was generally smaller in the less developed states than in the more developed states. The increase in the burden of depressive disorders, anxiety disorders, Panic disorders, Social phobia, and bipolar disorder was driven by the ageing of the population because age-standardisation nullified this increase. To study the levels of, sodium, potassium and calcium in psychiatric disorders.The present study includes total 100 subjects were selected for study. Out of which 50 were age and sex matched normal healthy control, 50 were suffered from psychiatric disorders. Blood sample were collected, and Electrolyte levels were measured by electrolyte analyzer, as electrolyte analyzer has different electrodes, specific for different ions of interest. Each electrode has an ion selective membrane that undergoes a specific reaction with the corresponding ions contained in the sample being analyzed.In our study the mean sodium levels in cases as 131.52±2.099 and in controls it was 137.98±6.06 (P